A Comprehensive Study of Underground Animals Habitat; Journal of Physics: Conference Series; Vol. 671 : Innovations in Non-Destructive Testing (SibTest 2015) - Klokov A. V.; Zapasnoy A. S.; Mironchev A. S.; Yakubov V. P.; Shipilova S. S. Svetlana Sergeevna (2016, 2016)
Title screen